Judicial Interpretation of the Principle of Equality Before the Law in Maintaining Impartiality in the Handling of Pro Bono Cases at the Surakarta District Court - Welly Cahya Saputra; Achmad Miftah Farid (Proceeding International Conference Restructuring and Transforming Law, 2026)
The principle of equality before the law affirms that everyone has equal standing before the law without distinction of social or economic background. This principle relates to the fulfillment of access to justice, including through the provision of free legal aid (pro bono) for the underprivileged. This study aims to examine (1) how judges at the Surakarta District Court interpret the principle of equality before the law in the matter pro bono; and (2) how judges apply the principle of equality before the law to maintain impartiality in the judicial process pro bono. This study uses an empirical legal research method with a socio-legal approach and case studies. Data were obtained through interviews, observations, and literature studies, then analyzed qualitatively. The results show that judges at the Surakarta District Court interpret the principle of equality before the law as the equal standing before the court, regardless of economic background or legal aid status. Judges assess cases based on the arguments, evidence, and facts revealed in court. The application of this principle is reflected in the provision of equal opportunity to the parties in court, from the presentation of arguments, the submission of evidence, witness examination, to the delivery of legal opinions. The judge's neutral attitude in presiding over the trial and the preparation of legal considerations based on facts and legal provisions are also part of efforts to maintain impartiality in case handling pro bono.